Currency Allocation of Public External Debt and Synchronization Indicators of Exchange Rate Volatility - Melecky, Martin (2012)
This paper uses synchronization indicators of domestic and foreign fundamentals to choose suitable currency allocation of public external debt. The selection of explanatory variables for exchange rate volatility is motivated using a New Keynesian Policy model that predicts that not only traditional optimum currency area (OCA) variables, but also variables considered by the literature on currency preferences, such as money velocity, should be relevant for explaining exchange rate volatility. I find that measures of inflation synchronization, money velocity synchronization, and interest rate synchronization are useful indicators for deciding on the currency denomination of public external debt.